Nanopatterned polymer brushes by reactive writing. Issue 14 (23rd February 2016) - Nawroth, Jonas F.; Neisser, Claudia; Erbe, Artur; Jordan, Rainer
Abstract : A self-assembled monolayer of perflourinated silanes is used to prepare nanopatterned polymer brushes and brush gradients by focused electron beam reactive writing (RW) and surface-initiated photopolymerization of vinyl monomers. Abstract : Polymer brush patterns were prepared by a combination of electron beam induced damage in self-assembled monolayers (SAMs), creating a stable carbonaceous deposit, and consecutive self-initiated photografting and photopolymerization (SIPGP). This newly applied technique, reactive writing (RW), is investigated with 1 H, 1 H, 2 H, 2 H -perfluorooctyltriethoxysilane SAM (PF-SAM) on silicon oxide, which, when modified by RW, can be selectively functionalized by SIPGP. With the monomer N, N -dimethylaminoethyl methacrylate (DMAEMA), we demonstrate the straightforward formation of polymer brush gradients and single polymer lines of sub-100 nm lateral dimensions, with high contrast to the PF-SAM background. The lithography parameters acceleration voltage, irradiation dose, beam current and dwell time were systematically varied to identify the optimal conditions for the maximum conversion of the SAM into a carbonaceous deposit. The results of this approach were compared to patterns prepared by carbon templating (CT) under analogous conditions, revealing a dwell time dependency, which differs from earlier reports. This new technique expands the range of CT by giving the opportunity to not only vary the chemistry of the created polymer patterns with monomer choice but also vary the chemistry of the surrounding substrate.